Status of the structure, process and outcoms of pharmaceutical care to HIV patient in Spain. Origen study - R. Morillo-Verdugo; R. Jiménez-Galán; O. Ibarra Barrueta; M. Martín Conde; L. Margusino Framinan; A. Illaro Uranga (Farmacia Hospitalaria)
Objectives: To describe the structure, process and outcomes with which hospital pharmacist performs health care activity, teaching and research about Pharmaceutical Care (PC) in HIV patients in Spain. Methods: Observational, cross-sectional and multicenter study carried out between November 2011-February 2012 in spanish hospitals. The inclusion criteria were: hospitals pharmacy services that dispensed antiretroviral medication to HIV patients. The questionnaire had 41 questions structured in 9 groups: hospital type and person conducting the survey, structure and resources, health care activities, interventions, communication with the rest of the multidisciplinary team, adherence, and quality records, management and pharmacoeconomy and teaching and research. Descriptive analysis was performed. To analyze the existence of statistically significant relationships, we applied fisher test, chi-square or logistic regression Results: 86 hospitals completed the survey. In 93%, PC consultation was not classified by pathologies. 27.9% provided continuing PC to all patients. Adherence was determined regularly or when pharmacist suspected poor adherence (57.5 %). 20% of hospital s teaching had a program that allowed a high level of training in PC to HIV patient. 52,3% of participating centers had published scientific articles related to HIV. Conclusions: Pharmaceutical care to HIV patients in Spain need to adapt to a new situation. For this, hospital pharmacists have to consider several issues such as chronicity, comorbidity, incorporation of new technologies and the stratification of patients in order to make it more efficient.